A review of magnetoencephalography use in pediatric epilepsy: an update on best practice. (2nd November 2021) - Otsubo, Hiroshi; Ogawa, Hiroshi; Pang, Elizabeth; Wong, Simeon M; Ibrahim, George M; Widjaja, Elysa
ABSTRACT: Introduction : Magnetoencephalography (MEG) is a noninvasive technique that is used for presurgical evaluation of children with drug-resistant epilepsy (DRE). Areas covered : The contributions of MEG for localizing the epileptogenic zone are discussed, in particular in extra-temporal lobe epilepsy and focal cortical dysplasia, which are common in children, as well as in difficult to localize epilepsy such as operculo-insular epilepsy. Further, the authors review current evidence on MEG for mapping eloquent cortex, its performance, application in clinical practice, and potential challenges. Expert opinion : MEG could change the clinical management of children with DRE by directing placement of intracranial electrodes thereby enhancing their yield. With improved identification of a circumscribed epileptogenic zone, MEG could render more patients as suitable candidates for epilepsy surgery and increase utilization of surgery.